(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, the modern educator aims to engage not only with children but also with the educational, cultural, and spiritual-educational upbringing of adults. In the Republic of Uzbekistan, it is approached as the main means of forming the spirituality of a harmoniously developed personality. Reflections are made on the basics of pedagogical methods for improving the socio-political worldview of future teachers.